Clinical manifestations of acute asthma in children at the Department of Child Health Cipto Mangunkusumo Hospital - Kadek Ayu Lestari; Imam Budiman; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2016)
Background Acute asthma is an asthma attack or worsening of asthma manifestation and pulmonary function. Severe asthma at- tack might be prevented by early recognition of the attack and ap- propriate therapy. Clinical manifestations of asthma in children vary widely, so does the assessment of the attack that is often not accu- rately defined by doctors. This leads to delayed and inadequate treatment of the attack. Objective This study aimed to know the clinical manifestations of acute asthma in children at the Department of Child Health, Medi- cal School University of Indonesia/Cipto Mangunkusumo Hospi- tal. Methods This was a descriptive, cross sectional study, conducted at the emergency room (ER), the Pediatric Pulmonology Outpa- tient Clinic, and the Pediatric Outpatient Clinic. Subjects were asth- matics who were having attack and aged 2-18 year-old. Data of age, sex, pulse rate, respiratory rate, duration of attack, expiratory, and inspiratory effort signs were obtained by history and physical examination followed by the assessment of attack severity. Results Subjects consisted of 92 children, mostly obtained from the ER (40%), with male to female ratio of 1.5:1 and average age of 5.8 years old. Most of the subjects had mild attack (83%) and duration of attack of less than 24 hours (56%). Most subjects (70%) only had signs of increased expiratory effort, in which all of them had mild attack. The rest of the subjects showed the combination of inspiratory and expiratory efforts; 12 patients with mild attack, 15 with moderate attack, and 1 with severe attack. Conclusion Patients who only showed expiratory effort usually had mild attack. Patients showing expiratory and inspiratory ef- forts usually had mild or moderate attack. Treatment should be tailored to the degree of attack